Kontribusi Motivasi Belajar dan Kompetensi Pedagogik Guru Terhadap Hasil Belajar Mata Diklat Keterampilan Komputer dan Pengelolaan Informasi (KKPI) Siswa Kelas X di SMK Negeri 1 Tilatang Kamang - Ilham Adi Putra; Zulkifli Naansah; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research is purposed to reveal scales of student’s learning motivation contribution and pedagogical competence of teachers grade for computer and information management skills subject at X class SMKN 1 Tilatang Kamang. The type of this research is descriptive correlation. Populations in this research are 164 students, and samples are amount to 62 students of X class SMKN 1 Tilatang Kamang, school of year 2012/2013. Samples are taken by simple random sampling technique. Data were collected by questionnaire and documentation. Data analysis technique in this research is Pearson product moment and multiple-correlation. Results from data analysis claimed that there are contributions from learning motivation and pedagogical competence of teachers grade of computer and information management skills subject at X class SMKN 1 Tilatang Kamang, as follow: (1) student’s learning motivation gives contribution to student’s grade by 21,34%, (2) pedagogical competence of teachers gives contribution to student’s grade by 17,89%, (3) student’s motivation to learn together with pedagogical competence of teachers give contribution to student’s grade by 27,98%. This research suggest that student’s motivation to learn and pedagogical competence of teachers give contribution to student’s grade.